ALGORITHMIC AND SOFTWARE IMPLEMENTATION OF E-TEXTBOOK “FUNDAMENTALS OF THEORY OF ELECTRONIC CIRCUITS” - Bobalo, Yuriy; Mandziy, Bogdan; Stakhiv, Petro; Shakhovska, Natalya (International Journal of Computing, 2014)
The paper presents the experience of developing electronic textbook “Fundamentals of the theory of electronic circuits”. The concept and development principles of electronic text book are discussed. The procedure of knowledge control and evaluation is described in details. The algorithm of automatic control the test tasks with possibilities of entering mathematical expressions is developed.